PROSEDUR PEMBUATAN NOMOR INDUK BERUSAHA (NIB) BAGI PELAKU UMKM MELALUI ONLINE SINGLE SUBMISSION (OSS) DENGAN PENERAPAN PRINSIP AKUNTANSI DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPM PTSP) PROVINSI JAMBI - Sinambela, Yohana Putri Lopian; Putra, Dios Nugraha (Jurusan Akuntansi FEB Universitas Jambi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in economic development; however, many still lack formal business legality, particularly the Business Identification Number (NIB). The government has introduced the Online Single Submission (OSS) system as an integrated electronic business licensing platform to simplify the registration process. This study aims to analyze the procedure for obtaining an NIB through the OSS system and to examine the role of accounting principles in supporting MSMEs during the registration process at the Investment and One-Stop Integrated Service Office (DPM PTSP) of Jambi Province. This research employs a qualitative descriptive method using observation, interviews, and documentation. The findings indicate that the NIB registration procedure has been implemented in accordance with regulations.